USING STREPTOMYCES XYLANASE TO PRODUCE XYLOOLIGOSACHARIDE FROM CORNCOB - MERYANDINI, ANJA; SUNARTI, TITI CANDRA; NAOMI, APRILIA; MUTIA, FERY (BIOTROPIA, 2008)
Streptomyces 234P-16 and SKK1-8 are xylanase-producing bacteria. Corncob xylan were extracted using acidified method. Crude enzymes (produced by centrifuging the culture) were used to hydrolyze xylan from 2 varieties of corncob. Crude extract activity was measured by using DNS (Dinitrosalisilic Acid) method. Xylanase from strain 234P-16 has the highest activity if cultivated in 1% Hawaii xylan, whereas strain SKK1-8 on 1.5% Bisma xylan. SKK1-8 xylanase can hydrolize corncob xylan (1% Hawaii or 1.5% Bisma xylan) within 4 hours and produce xylooligosacharide with polymerization degree of 4.76 and 6.37, respectively. Key words: Xylanase, Xylooligosacharide, Streptomyces.